The concept of resilience in OSH management: a review of approaches. Issue 2 (2nd April 2016) - Pęciłło, Małgorzata
Abstract : The concept of resilience has become very popular, especially in the 21st century. This concept is applicable to many fields, from mechanics to a broad range of social sciences. Resilience has even become part of the national and global policies of the USA, the United Nations and the European Commission. The concept of resilience has also been implemented in the area of safety and health based on the criticism of the traditional approach to occupational safety and health, which does not result in a satisfactory level of occupational safety. The concept of resilience was adopted to research occupational safety and health in different fields and thus with different approaches, such as via socio-technical studies, the psychological and behavioral aspects of organizational resilience and the link with research on individual or family resilience and its influence on work.